IoT Application, A Survey - Devi Kotha, Harika; Mnssvkr Gupta, V (International Journal of Engineering and Technology, 2018)
Internet of Things ( IoT ) , where physical systems are connected over network to exchange information among themselves and with their surroundings. IoT helps in developing  most powerful industrial systems. It  finds its various applications in house hold, agriculture, and in various industrial systems. In an effort to understand the growth of IoT , this paper reviews current research trends of IoT , key technologies, and its major applications, and identifies  key challenges of IoT. This paper mainly summarizes the applications of  IoT in industries